EDUKASI PELESTARIAN MANGROVE BAGI MASYARAKAT SEBAGAI UPAYA MITIGASI BENCANA DI DESA BOSUA KABUPATEN MENTAWAI - Yessy Markolinda; Sawirman Sawirman; Mery Ramadani; Fitri Yusya; Nadiyatul Husna; Rezi Fatrima Surya; Fadilla Azmi; Mira Lilia D.B.P; Rd. Aldifa Taufiqurrahman; Christi Yolanda (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
The aim of this activity is to educate and empower the community to actively participate in conservation efforts, which involves mangrove planting mutual cooperation activities, the formation of environmental awareness groups, and collaboration with NGOs, government, and academics. The activity methods used are providing education using lectures, educational videos, distributing flyers and posters and planting mangrove seedlings on the beach. To measure the success of education, pre tests and post tests were used to measure the level of community knowledge about mangrove forest conservation. The results of this activity increased community knowledge by 6.13, from 12.53 (before education) to 18.66 (after education). The T-test results obtained a p-value <0.001. That is, statistically it can be concluded that there is a significant average difference between community knowledge before and after education. The conclusion of this activity is that after being given education, the average community has increased knowledge about mangrove forest conservation as an effort to reduce disaster risk. It is hoped that the community and local government will be able to maintain and preserve mangrove forests in the Bosua Village area as a form of effort in disaster mitigation.